Exploring the structural and functional requirements of Phyto-compounds and their synthetic scaffolds as anticancer agents: Medicinal chemistry perspective - Dipanjan Karati; Dileep Kumar (Pharmacological Research - Modern Chinese Medicine, 2022)
Cancer is the second most reason for huge mortality in human life which has attributed to a drastic drift in anticancer drug discovery and development. Small molecules as anticancer agents have contributed tremendously for the treatment of cancer however plants based natural products have the cardinal foundation for traditional medicine schemes and still offer relief to cancer patients. Medicinal plants are known for producing numerous bioactive secondary metabolites that have been used since antiquity due to their medicinal properties. Copious advantages of natural products over conventional anticancer drugs have expanded their use in the health care industry which has been witnessed by the extensive use of natural products in the treatment of multiple cancers. The pleiotropic effects of plant products on targets in multiple ways, phytochemicals are considered as suitable source candidates for anticancer drug design and development. In this review, we attempted to compile structural and functional attributes of natural products with an emphasis on their anticancer properties.